Advanced craniosacral therapy a combination of Quantum theories and Einstein's relativities - Cobra Ghasemi (Archive of Biomedical Science and Engineering - Peertechz Publications, 2020)
As I noticed, some obvious points are missed in recent correspondence in the International Journal of Osteopathic Medicine considering the mechanism and effectiveness of Craniosacral therapy. considering phenomena of Craniosacral therapy as a placebo and statistical regression won't be dismissed. The recognition of Mr. Maddick's that the present explanatory model is useless should be commended [1].